Oxidative nucleophilic aromatic amination of nitrobenzenes. Issue 45 (6th May 2016) - Khutorianskyi, V. V.; Sonawane, M.; Pošta, M.; Klepetářová, B.; Beier, P.
Abstract : Regioselective oxidative nucleophilic substitution of aromatic hydrogen of substituted nitrobenzenes with lithium salts of arylamines is described. The method allows the synthesis of a variety of N -aryl-2-nitroanilines. Abstract : Nitrobenzenes substituted with electron-acceptor groups such as halogen, nitro, trifluoromethyl, pentafluorosulfanyl, or cyano underwent oxidative nucleophilic substitution with lithium salts of arylamines to afford N -aryl-2-nitroanilines.